Improvement of induction machine performance using power factor correction - Ismail, Daut, Prof. Dr.; Mohd Irwan, Yusoff; Muhammad Irwanto; Safwati, Ibrahim; Gomesh Nair, Shasidharan; Ezzani, M.; Risnidar, Chan (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/